Análisis de los criterios de eficiencia económica y calidad para la determinación de las tarifas del sector eléctrico en Colombia (2003)
The subject of the economic and quality efficiency has great importance in the decision on the electric service fairs in Colombia and on the economical analysis of the effects on the social welfare of the consumers and the companies that provides the service. At the beginning of this article is a brief description of the way the electric sector works, and then there is a description of the principles, that according to the law must be considered for such fairs, explaining the economical and quality, efficiency and some experiences in South America regarding the quality criteria.